The extraction of vitex pouch / A. Mohd Ali [et al.]... - A., Mohd Ali; Jahidin, Aisyah Hasyila; Abdul Wahab, Ibtisam; Mohsin, Hannis Fadzillah; Hazizul Hasan, Mizaton (Dr.) (Universiti Teknologi MARA, Negeri Sembilan, 2018)
In this study, the unprecedented extraction of the Vitex pouch was performed. The compounds from methanolic and chloroform extracts were isolated by using thin layer chromatography (TLC). The compound of interest was investigated by using 1 H-Nuclear Magnetic Resonance (NMR, 500 MHz) spectroscopy. From the NMR spectral examination, the compound from the methanolic extract was suggested as glucononitol. Indeed, there are some parameters that could enhance the attainment of this research, which include high performance liquid chromatographic supplies. Nevertheless, more information and understanding on the pharmaceutical and chemical analysis of the Vitex species were obtained. To sum up, it is anticipated that incoming research with advanced technology for thisnatural product could be explored in the future.